Dating postwar business cycles : methods and their application to Western Germany (1950-67) - Mintz, Ilse (New York : National Bureau of Economic Research; distributed by Columbia University Press, 1969)
This book seeks to determine the historical turning points of West German business cycles. For purposes of identifying cycles, she rejects any sole reliance upon quarterly GNP data. Instead she examines the behaviour of 21 time series that is 8 quarterly ones (inclusive of GNP at current and at constant prices) and 13 monthly ones, which combined are presented as the reference business cycles.
Bibliographical footnotes.
lje 12/12/18
Loans
Keywords: Business cycles; Germany (West)